Dentists’ Knowledge, Attitude, and Practice Regarding Evidence-Based Dentistry Practice in Riyadh, Saudi Arabia - ALmalki, Waleed Daifallah (J Pharm Bioallied Sci, 2019)
OBJECTIVE: The aim of this study was to assess the existing level knowledge and the use of evidence-based dentistry among dental clinicians. METHODS AND MATERIALS: A cross-sectional questionnaire-based survey was conducted among 400 male and female dental practitioner’s working in academic, governmental, and private sectors in Riyadh, Saudi Arabia. RESULTS: In this study, a total of 400 subjects were recruited of whom 253 (63.3%) were male dental practitioners and 147 (36.8%) were female dental practitioners: 229 (57.3%) subjects belonged to 25–34 age group, 145 (36.3%) to 35–44 age group, 18 (4.5%) to 45–54 age group, and 8 (2%) to >55 age group. Among them, 202 (50.5%) were mixed practice, 91 (22.8%) were working in academics, 76 (19%) belonged to private practice, and 31 (7.8%) belonged to government practice. In addition, 225 (56.3%) were general practitioners and postgraduates, 86 (21.5%) were specialists, 47 (11.8%) were consultants, and 42 (10.5%) had other qualifications. In total, 221 (55.3%) subjects completed their qualification within before 1–5 years, 153 (38.3%) completed their qualification within before 6–10 years, 19 (4.8%) completed their qualification within before 11–15 years, and 7 (1.8%) completed their qualification within 16–20 years. CONCLUSION: This survey mirrors the necessity to conduct continuing dental education programs on evidence-based practice (EBP), so as to give the dentists of Riyadh better knowledge regarding EBP so that they can administer it in their daily clinical practice and deliver better quality care to their patients.